Experimental Astronomy Astrophysical Instrumentation and Methods - von Ballmoos, Peter; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Many new instruments for observing astronomical objects at a variety of wavelengths have been and are continually being developed. Furthermore, a vast amount of effort is being put into the development of new techniques for data analysis in order to cope with great streams of data collected by these instruments. Experimental Astronomy acts as a medium for the publication of papers of contemporary scientific interest on astrophysical instrumentation and methods necessary for the conduct of astronomy at all wavelength fields. Experimental Astronomy publishes full-length articles, research letters and reviews on developments in detection techniques, instruments, and data analysis and image processing techniques. Occasional special issues are published, giving an in-depth presentation of the instrumentation and/or analysis connected with specific projects, such as satellite experiments or ground-based telescopes, or of specialized techniques. .
Keywords: Observations, Astronomical; Astronomy -- Observations; Astronomy, Observations and Techniques; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences